IMPLEMENTATION OF VIRTUAL PLATFORM IN HUMAN TALENT TO THE PYMES OF THE DIDACTIC COMPANY AGH SAS - Arevalo Hernandez, Franklin Giovanni
The Virtual platforms and web portals have become tools that promote, facilitate and dynamize communication processes between different people in a synchronous and adaptable way. It follows from the above that the opportunity to use the advisory service through the virtual platform as a tool to facilitate the training of the of the Administrative Management Center apprentices in the Human Talent Coordination, by means of the technology, in a way that involves the virtual services, in order that the apprentices can simulate a business environment through the participation of forums and an interactive chat, which not only manages to deal with exclusive technology issues, but motivate them to participate actively in discussions that arise in the customer inquiry or supported SMEs; which will generate in the apprentice the developement of reading, analysis and exploration skill in different points of view, with solid arguments that promote the dialogue of knowledge, critical thinking and the social construction of knowledge related to Human Talent Management. This strategy is guided based on the advice provided by the AGH SAS Company didactical approach, in strengthening its service and facilitating communication with its customers and employees, using business innovation and ensuring an effectiveness in the process of Human Talent Management.